Unintentional recurrent laryngeal nerve injuries following thyroidectomy: Is it the surgeon who pays the bill?. (May 2017) - Gambardella, C.; Polistena, A.; Sanguinetti, A.; Patrone, R.; Napolitano, S.; Esposito, D.; Testa, D.; Marotta, V.; Faggiano, A.; Calò, P.G.; Avenia, N.; Conzo, G.
Abstract: Background: Thyroidectomy is one of the most common intervention in general surgery and, after the turn of the century, its rate has sharply increased, along with a worldwide increased incidence of differentiated thyroid cancers. Therefore, injuries of the recurrent laryngeal nerve have become one of the most frequent cause of surgical malpractice claims, mostly following surgery for benign pathology. Main body: Even if the incidence of definitive paralysis is generally lower than 3%, during the last 20 years in Italy, the number of claims for damages has sharply raised. As a consequence, a lot of defensive medicine has been caused by this issue, and a witch-hunt has been accordingly triggered, so determining mostly a painful and lasting frustration for the surgeons, who sometimes are compelled to pay a lot of money for increasing insurance premiums and lawyers fees. Recurrent laryngeal nerve injury should be considered as a potentially catastrophic predictable but not preventable event, rather than the result of a surgical mistake. Conclusion: Purposes of the Authors are analyzing incidence, conditions of risk, and mechanisms of recurrent laryngeal nerve injuries, underlining notes of surgical technique and defining medical practice recommendations useful to reduce the risk of malpractice lawsuits and judgments against surgeons. Highlights: Injury of Recurrent Laryngeal Nerve has become one of the most frequent cause of medicolegal lawsuit. The incidence of unintentional RLN injury is 1–2% in tertiary referral centers, testifying that, also in experienced hands, it is a predictable but not preventable event at all. What is the value and meaning of an informed consent?